2019
DOI: 10.1029/2019ja026629
|View full text |Cite
|
Sign up to set email alerts
|

The Difference Between Isolated Flux Transfer Events and Flux Transfer Event Cascades

Abstract: This flux transfer event (FTE) study is based on 984 FTEs originally identified by Wang et al. (2005, https://doi:10.1029/2005JA011150) in Cluster data. Due to Cluster's orbit, the FTE list exclusively contains events detected at the high‐latitude dayside magnetopause and low‐latitude flanks. The focus of this study is on FTE separation time. The results show that FTEs appearing in cascades are mainly located at the northern dusk and southern dawn magnetopause, while isolated FTEs are equally spread over the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Although the cascade of FTEs may occur during a northward IMF (Kullen et al, 2019) and under stable IMF conditions, it is worth noting that the observed EMRFs during this period were not accompanied by correlated variations in solar wind and IMF conditions. This implies that the intermittent lobe reconnections were not directly driven by changes in solar wind or IMF.…”
Section: Intermittent Lobe Reconnection Reflected By Emrfsmentioning
confidence: 80%
See 2 more Smart Citations
“…Although the cascade of FTEs may occur during a northward IMF (Kullen et al, 2019) and under stable IMF conditions, it is worth noting that the observed EMRFs during this period were not accompanied by correlated variations in solar wind and IMF conditions. This implies that the intermittent lobe reconnections were not directly driven by changes in solar wind or IMF.…”
Section: Intermittent Lobe Reconnection Reflected By Emrfsmentioning
confidence: 80%
“…This discovery holds particular significance in advancing our understanding of the solar wind-magnetosphere coupling process in the cusp region. which appear quasi-periodically in cascades of up to 10 FTEs in succession (Farrugia et al, 1987;Kullen et al, 2019). Therefore, it is puzzling why the lobe reconnection under prolonged northward IMF conditions should be always continuous.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Kullen et al. (2019) studied the occurrence of two different types of flux transfer events (FTEs): FTE cascades with separation times <70 min and isolated FTEs with separation times ≥70 min. They found that while only 2–50.17em% of FTE cascades in their data set occurred during low IMF cone angle (<30°) conditions, 160.17em% of isolated FTEs occurred during these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, they concluded that these fluctuations do not cause reconnection and argued that the timescale of the fluctuations is probably too short for reconnection. However, Kullen et al (2019) studied the occurrence of two different types of flux transfer events (FTEs): FTE cascades with separation times <70 min and isolated FTEs with separation times ≥70 min. They found that while only 2-5% of FTE cascades in their data set occurred during low IMF cone angle (<30  ) conditions, 16% of isolated FTEs occurred during these conditions.…”
mentioning
confidence: 99%